Analisis Pengaruh Strategi Konten Sosial Media Terhadap Aplikasi Layanan Streaming - Dedy Kurniawan; Ali Ibrahim; Endang Lestari Ruskan; Khairunnisa (AI Society & STMIK Indonesia, 2023)
Social media marketing is becoming a key strategy for streaming applications. This study analyzes the content strategy of the Instagram account @Netflixid and its impact on customer loyalty. The study uses a quantitative approach with an online survey as a data collection method and Structural Equation Modeling (SEM)-Partial Least Squares (PLS) as a research method. The results show that content that reflects the behavior of followers and is animated is preferred by Netflixid audiences. This content strategy also has a positive impact on customer loyalty.